PENGARUH PENGANGGURAN DAN KEMISKINAN TERHADAP TINDAKAN KRIMINAL DI KABUPATEN TOLITOLI PERIODE 2012-2021 - Fitri S Kasim; Hendra Hendra (Laboratorium Riset Ekonomi, 2023)
The purpose of this study was to see how unemployment and poverty affect criminal behavior in Tolitoli Regency. The data analysis approach used in this research is multiple linear regression, and the type of data used is secondary data obtained from the Central Bureau of Statistics (BPS) and Tolitoli District Police. The results of this study indicate that (1) In Tolitoli Regency, unemployment has a negative and small impact on criminal activity. (2) Poverty has a positive but small impact on criminal activity in Tolitoli Regency.